Effect of High Dose Acetaminophen on Liver Function Tests in Healthy Subjects - Kumagai, Y.; Song, I.D.; Maeda, M.; Tanaka, R.; Sakamoto, Y.; Aso, M.; Saito, Y.; Maekawa, K.; Fujita, T. (Clinical Therapeutics, 2017)
Liver function was monitored by AST, ALT, ALP and HMGB-1 (high mobility group box-1), and subjects who showed increase in LFT over twice of upper limit of normal were withdrawn from the study. The study was approved by the institutional review board of Kitasato University Hospital and performed after obtaining...